Urban morphology and medieval burgh development in Edinburgh and Elgin (Proceedings of the Society of Antiquaries of Scotland, 2011)
Presented here are the results of a study to assess the potential of urban morphology to make a continuing contribution to the understanding of urban development in the Scottish burghs and to provide helpful input to associated archaeological studies. Use is made of recent cartographically based evidence of the high degree of consistency and stability to be found in the configuration of the burgage plots and foreland lines in Scottish burghs.To do this, four carefully selected aspects of the urban development, one in Edinburgh and three in Elgin, were examined. The two Scottish burghs were selected for their similarity of layout along a single main street, providing a relatively simple urban pattern. For Edinburgh, appropriate morphological information, which is available from earlier studies, is summarised. Similar information for Elgin was compiled as part of this study and the results are set out.The case is made that urban morphology still has much to offer in the study of Scottish urban history and archaeology. In addition, having reviewed recent archaeological reports, it is suggested that archaeology has great potential to provide a strong contribution to the better understanding of the urban morphology of Scotland.